Implementation of project conducted in foreign language classroom (Вестник КазНУ. Серия Востоковедения, 2018)
This article describes the implementation of project works in foreign language classroom, which isbased on project based learning method. There is always a solution of problem in the project methodand it always aims at obtaining the result. The method of projects is thus the organized search, researchactivity of students, which involves not just the achievement of a particular result, formalized in the formof a concrete practical homework, but the organization of the process of achieving this result. The studyshows all the possible variations of organizing projects related to learning languages in an appropriateway.